SUMPAH ALLAH DALAM AL-QUR’AN: KONSEP DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM: Konsep dan Implikasinya terhadap Pendidikan - Rifkoh, Zainatur; Islamiyah (Rihlah Review: Jurnal Pendidikan Islam, 2026)
This research examines the phenomenon of Allah’s oaths distributed across various surahs in the Qur’an. An oath constitutes a unique linguistic style in which the Creator swears by His own Name or by His creations, such as the sun, time, or the fig tree. The primary problem addressed in this study is why Allah—who is the source of absolute truth—needs to swear an oath, and what profound messages underlie the invocation of created entities within those oaths. The research employs a qualitative methodology with a library research approach, utilizing a descriptive-analytical analysis of both classical and contemporary books of exegesis (tafsir). The findings indicate that Allah’s oaths serve as a form of emphasis to eliminate doubt for the reader regarding the veracity of the message delivered following the oath. Furthermore, there are educational and scientific implications that encourage humanity to engage in deep reflection upon the objects of these oaths. Allah’s oaths also imply the vital importance of educational curricula and instruments. Human integrity and moral responsibility in education encompass instruments, curriculum, and time management, all aimed at fostering a sustainable culture of educational quality.